Argumentation and Interpretation. Argumentative Practice as a Cultural Activity - Gałkowski, Paweł (Sensus Historiae, 2024)
Persuasive argumentation in everyday communication is most often viewed through the prism of its performative effectiveness. This is not surprising, after all, persuasion as commonly understood is supposed to be accurate and persuasive. Less often do we consider what role interpretation plays in the persuasive process, or more broadly, what senses the activity of argumentation carries. This is a pity, because the trail of interpreting argumentative statements can lead us to an important, from a methodological perspective, question: are arguments activities or products subject to scientific explanation? In this article, I try to follow the methodological threads that bring persuasive argumentation together with humanistic interpretation as well as with the socio-regulatory concept of culture and the reflection cultivated within the Poznan School of Methodology.